DEVELOPMENT OF MATHEMATICS MODULE BASED ON ARIAS MODEL ON THE MATERIAL OF ALGEBRAIC FORM FOR GRADE VII - Ami Ramadayanti; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Development of Mathematics Module Based on ARIAS Model on the Material of Algebraic Form For Junior High School Grade VII 1ST Semester. The problems that were found are limited availability of teaching materials causes the learning process to be less varied and teacher-centered, so the student's independence and activeness in building their knowledge below. This research aims to develop, test the modules' feasibility, and determine student responses to modules with the ARIAS model on algebraic form material. The research design used is Research and Development. The research subject is material experts, media experts, and students from Junior High School (SMP) Muhammadiyah 04 Yogyakarta and SMPN 03 Pleret. Data collection techniques were used through interviews and questionnaires with teachers and students. The instrument was tested through validation from material experts and media experts. Data analysis used questionnaire analysis and analysis of the feasibility of the mathematics module. The results showed that the module's assessment by material experts obtained an average score of 106,33 with very good. The module's assessment by media experts obtained an average score of 131 with thry good. The student's response obtained an average score of 114,83 with the category of very good. Based on the calculations' results, it can be concluded that the mathematics module was feasible to be used in the learning process.